2009
DOI: 10.1111/j.1472-765x.2009.02596.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival ofSalmonellaon refrigerated chicken carcasses and subsequent transfer to cutting board

Abstract: Objective:  To determine the effect of refrigeration time and temperature on Salmonella cell numbers on inoculated chicken carcasses and their transfer to a plastic cutting board. Methods and Results:  The survival of Salmonella on chicken skin and the transfer to a plastic cutting board when exposed to different refrigeration temperatures (2, 6 or 8°C) for 9 days were the two main issues on which this work focused. Two scenarios were carried out to ascertain these effects: carcasses treated with a decontamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
0
19
1
1
Order By: Relevance
“…According to Jimenez et al [2009], levels of Salmonella from chicken skin to cutting boards showed approximately a 1.5 log difference, which is lower than the results of the present study (ca. 3 log difference).…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…According to Jimenez et al [2009], levels of Salmonella from chicken skin to cutting boards showed approximately a 1.5 log difference, which is lower than the results of the present study (ca. 3 log difference).…”
Section: Resultscontrasting
confidence: 94%
“…Cross-contamination between cutting boards and foods during food preparation is a common factor causing food poisoning [Chiu et al, 2006;Ravishankar et al, 2010]. Although the load of this contamination and the number of cells transferred to cutting boards is low, this low transfer amount can cause a health risk through temperature abuse, high virulence, and susceptible consumers [de Boer and Hahne, 1990;Jimenez et al, 2009]. Moreover, E. coli O157:H7 can cause foodborne illness with low infection doses of <10 cells [Buchanan and Doyle, 1997].…”
mentioning
confidence: 99%
“…In a study conducted in a commercial abattoir, Bolton et al (2002) reported an increase in total viable bacterial counts from 3.8 to 4.5 log cfu/cm 2 on carcasses at the refrigeration stage. Another study conducted on poultry carcasses showed that after 9 days of storage, Salmonella loads were slightly reduced (by less than 1 log unit) on carcasses refrigerated at 2 and 6°C whereas in carcasses refrigerated at 8°C Salmonella number increased by 1.5 log units (Jiménez, Tiburzi, Salsi, Moguilevsky, & Pirovani, 2009). …”
Section: Carcass Decontamination Treatmentsmentioning
confidence: 98%
“…Various origins of microbial contamination during cutting/boning were reported in literature. These include carcasses or meat pieces to be processed (McEvoy et al, 2004); meat cutting/boning equipments such as knives, meat conveyors or cutting boards (Gill, Badoni, & McGinnis, 1999;Gill et al, 2001;Jiménez et al, 2009) and soiled surfaces or operators (Sheridan, Lynch, & Harrington, 1992). One of the measures to prevent cross contaminations resulting from contaminated carcasses or meat pieces would be to identify the most contaminated raw materials and to process them separately preferably at the end of the production (Koohmaraie et al, 2012).…”
Section: Post Slaughter Contamination Of Bovine Meatmentioning
confidence: 99%
“…almonella has been associated with many food-borne diseases across the world (19). It is the cause of an estimated 1.4 million illnesses annually in the United States (25).…”
mentioning
confidence: 99%